Physicochemical and Rheological Properties of Sago (MetroxylonSagu) Starch Modified with Lactic Acid Hydrolysis and UV Rotary Drying - Siswo Sumardiono; Rizki B Rakhmawati; Isti Pudjihastuti (Department of Chemical Engineering, Universitas Gadjah Mada, 2019)
Modification of sago starch using acid hydrolysis will change some physicochemical and rheological properties. Sago is easy to grow in tropical areas of coastal areas, many found in eastern Indonesia has a simple ergonomic terms. Ingredients of sago starch is consist of 20-30% amylose and 70-80% amylopectin which make sago starch difficult to dissolve in cold water, easy to gelatinize, high viscosity, hard and not expands in baking process. This study will analyse modified sago using lactic acid hydrolysis method and use UV rotary drying for 20 minutes. The properties of modified sago starch were observed i.e. pH, density, solubility, swelling power, and baking expansion. Time variables hydrolysis is 10; 15; 20; 25; and 30 minutes with a rotation speed of 8 rpm at room temperature. The results showed that the solubility, swelling power and baking expansion was increase. The density results showed that the longer acid hydrolysis time can make the smaller in the density. Solubility and swelling power showed increasing significantly compared to native sago starch. Modification by using UV light changes significantly the properties characteristics of product.